2012
DOI: 10.1161/strokeaha.111.624551
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Early [ 18 F]-2-Fluoro-2-Deoxy-D-Glucose Positron Emission Tomography for Identifying Hypoperfusion and Predicting Fate of Tissue in a Rat Embolic Stroke Model

Abstract: Background and Purpose-Experimental stroke models are essential to study in vivo pathophysiological processes of focal cerebral ischemia. In this study, an embolic stroke model in rats was applied (1) to characterize early development of regional cerebral blood flow and metabolism with positron emission tomography (PET) using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Using PET, an increased uptake of FDG in regions with mild reduction of CBF was also reported in rats 75 minutes after MCAO. 9 However, this hyper-uptake pattern no longer existed 3 hours after MCAO in another study. 10 Nasu et al 11 imaged patients with stroke 1 to 7 days after cerebral ischemia using FDG PET, and hyper-accumulation of FDG was observed around the depressed uptake core in 7 of 20 patients.…”
mentioning
confidence: 89%
“…Using PET, an increased uptake of FDG in regions with mild reduction of CBF was also reported in rats 75 minutes after MCAO. 9 However, this hyper-uptake pattern no longer existed 3 hours after MCAO in another study. 10 Nasu et al 11 imaged patients with stroke 1 to 7 days after cerebral ischemia using FDG PET, and hyper-accumulation of FDG was observed around the depressed uptake core in 7 of 20 patients.…”
mentioning
confidence: 89%
“…In a rat model of contusion spinal cord injury (SCI), reductions in FDG uptake activity at the injury site were measured when compared to uninjured cord (Nandoe Tewarie et al, 2010). Rat models of ischemia have used FDG-PET to detect metabolic variations as markers of predicting tissue fate or recoverability (Fu et al, 2009; Walberer et al, 2012) and have shown FDG-PET to be more sensitive to metabolic alterations in the ischemic core at earlier time points post-injury (Sobrado et al, 2011). FDG-PET has also been useful for tracking novel treatment outcomes of ischemia, as demonstrated by recent work with transplantation of bone marrow stromal cells for improvement in cerebral glucose metabolism (Miyamoto et al, 2013).…”
Section: Fdg-pet and Tbimentioning
confidence: 99%
“…Two recent studies evaluated 18 F-FDG metabolism 75 minutes [54] and 3 hours [55] after MCAO using an ischemic stroke model, respectively. Sobrado et al carried out a longitudinal evaluation of 18 F-FDG metabolism and infarct size [55].…”
Section: Evaluation Of Glucose Metabolism In Ischemic Strokementioning
confidence: 99%